2016
DOI: 10.1039/c5dt04027b
|View full text |Cite
|
Sign up to set email alerts
|

Alkynyl bridged cyclometalated Ir2M2 clusters: impact of the heterometal in the photo- and electro-luminescence properties

Abstract: We report two unprecedent alkynyl bridging cyclometalated clus-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Although several papers reported the PL properties and application of cluster-type Ir-complexes on an ethynyl platform, 357,358 limited literature is available on pure Ir− acetylide σ-coordination complexes. 359,360 This is mainly attributed to the low stability of σ-acetylide complexes.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Although several papers reported the PL properties and application of cluster-type Ir-complexes on an ethynyl platform, 357,358 limited literature is available on pure Ir− acetylide σ-coordination complexes. 359,360 This is mainly attributed to the low stability of σ-acetylide complexes.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…However, only a few examples on the employment of multinuclear complexes in LEC devices exist in the scientific literature. [37][38][39][40][41][42][43] Bideh and Shahroosvand 37 and Ju et al 38 reported on ionic homodinuclear Ru complexes, which delivered strong emission with an external quantum efficiency (EQE) of 0.1-0.7% in LEC devices. Leprêtre and co-workers demonstrated non-ionic homodinuclear Ru complexes that exhibited orange emission in LECs with an EQE of 0.02 %, 39 while Fernandez-Cestau et al introduced novel heterotetranuclear Ir/Ag and Ir/Cu complexes equipped with alkynyl bridging ligands in LEC devices that delivered a peak luminance of ~20 cd/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Leprêtre and co-workers demonstrated non-ionic homodinuclear Ru complexes that exhibited orange emission in LECs with an EQE of 0.02 %, 39 while Fernandez-Cestau et al introduced novel heterotetranuclear Ir/Ag and Ir/Cu complexes equipped with alkynyl bridging ligands in LEC devices that delivered a peak luminance of ~20 cd/m 2 . 40 Finally, Sessolo and co-workers recently reported on LECs based on an ionic homodinuclear Ir complex that featured an EQE of 0.83%. 42 Accordingly, the use of multinuclear complexes in LEC is not yet as successful as in OLEDs and more comprehensive studies are needed in order to assess their full potential.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In a recent work, the structure and photophysical properties of two tetranuclear complexes based on Ir2M2 clusters (M = Ag or Cu), together with their diiridium precursor which is stabilized by a double alkynyl bridging system, were presented. [10] While electroluminescence from the tetranuclear complexes was indeed observed, LECs based on the dinuclear iridium compound were not fabricated. More recently, a highly luminescent pyrazolate-bridged platinum(II) complex was synthesized and used as the active layer in LECs, obtaining moderate luminescence intensity and lifetime.…”
mentioning
confidence: 99%